KEPRIBADIAN GURU DALAM DUNIA PENDIDIKAN - Tarmizi Situmorang (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
The teacher is a profession in education who have ups and downs, the teachersconsidered sacred profession and proud. This was seen when proudly bermenantukan ateacher. However, this time the teacher allegedly as a profession marginalized. It isevident from the many generations that little aspire to be a teacher, because the teacherdoes not have a large income, such as doctors, engineers, pilots and so forth. Teachertaught his students that are beneficial and useful knowledge for the benefit of mankind,teacher personality has its own advantages. However, there are those who say theteacher's personality is difficult to find the levels and not easy to find the limit and it isalso hard to be defined thoroughly.Keywords: Kepribadian, Guru, Pendidikan.